Motivasi Pemeran Utama dalam Melakukan Tour ke Eropa Pada Novel 2,578.0 Km Karya Ayu Nugraheni - Rosana Farah Widuri; Nadila Frida Natasya; Eva Dwi Kurniawan (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to determine the motivation of the main character to travel to Europe in the novel 2,578.0 KM by Ayu Nugraheni. This novel tells about the motivation of the two main characters who both have problems and divert these problems by going on a tour of Europe. This research method is descriptive qualitative with data collection techniques using notes and reading novels which are the research object. Aspects such as internal conflict, relationships between characters, and story development are also considered to understand the motivation for the main character's trip to Europe in the context of the story. The results of the research describe the characters of Juni and Elio, as well as their motivation for traveling to Europe on the overall development of the story.